Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Phân tích các đa thức sau thành nhân tử:
\(d,2x^2-3x-27\)
\(e,2x^2-5xy-3y^2\)
d) \(2x^2-3x-27\)
\(=\left(2x^2+6x\right)-\left(9x+27\right)\)
\(=2x\left(x+3\right)-9\left(x+3\right)\)
\(=\left(2x-9\right)\left(x+3\right)\)
e) \(2x^2-5xy-3y^2\)
\(=\left(2x^2+xy\right)-\left(6xy+3y^2\right)\)
\(=2x\left(x+y\right)-3y\left(x+y\right)\)
\(=\left(2x-3y\right)\left(x+y\right)\)
d) \(2x^2-3x-27\)
\(=\left(2x^2+6x\right)-\left(9x+27\right)\)
\(=2x\left(x+3\right)-9\left(x+3\right)\)
\(=\left(2x-9\right)\left(x+3\right)\)
e) \(2x^2-5xy-3y^2\)
\(=\left(2x^2+xy\right)-\left(6xy+3y^2\right)\)
\(=2x\left(x+y\right)-3y\left(x+y\right)\)
\(=\left(2x-3y\right)\left(x+y\right)\)